Finding the Routing Table by Dynamic Processing Method in Distance Vector Routing (International Journal of Engineering and Computer Science, 2017)
Distance vector routing is a routing protocol for communication methods used in packet-switched networks. It makes use of distance to decide the best path for forwarding the packets. DVRP (Distance Vector Routing Protocol) uses routing hardware to find distances to all nodes within a network. DVRP method uses mainly two factors – distances and vectors. Distance is the number of count it needs to reach to the destination and vector is the trajectory of the message through the given nodes. DVRP uses the Bellman-Ford equation for calculating the paths and for updating the routing tables. This paper proposes an approach for calculation and updating of routing tables which is based on Dynamic processing.